2018
DOI: 10.1093/ndt/gfy046
|View full text |Cite
|
Sign up to set email alerts
|

Treatment plans and outcomes in elderly patients reaching advanced chronic kidney disease

Abstract: These findings indicate that nephrology care should accommodate changes over time in older patients' treatment preferences and plans concerning dialysis. These changes are associated with whether, when and how these patients initiate dialysis but are not necessarily associated with post-dialysis survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…Considering that the risk factors for renal impairment, such as diabetes mellitus (DM) and hypertension, are increasing with improved life expectancy, renal dysfunction in the elderly is expected to become more frequent [2]. Since renal dysfunction is associated with higher morbidity and mortality in the elderly [2, 3], further studies are needed to assess and diagnose it in this population. Although several parameters have been reported as biomarkers for estimating renal function, few studies have explored them in the elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the risk factors for renal impairment, such as diabetes mellitus (DM) and hypertension, are increasing with improved life expectancy, renal dysfunction in the elderly is expected to become more frequent [2]. Since renal dysfunction is associated with higher morbidity and mortality in the elderly [2, 3], further studies are needed to assess and diagnose it in this population. Although several parameters have been reported as biomarkers for estimating renal function, few studies have explored them in the elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the study included a more significant number of patients (938) and was multicenter, it also had a smaller number of diabetic patients (23.8%) compared to the Japanese (37%), Turkish (41.4%) or in our study (30%), and could explain these differences, due to the higher mortality in diabetic patients (28). Similarly, the mean age of the Chinese patients was comparatively lower (52.8) than that of the patients in the Japanese (68), Turkish (73.8) and our studies (78.3), which is essential because older age is associated with higher mortality in CKD (29).…”
Section: Discussionmentioning
confidence: 44%
“…Several reports during the early 2000s suggested that in patients aged �75 years with multiple extrarenal comorbidities are unlikely to benefit from RRT in terms of the survival time outside the hospital setting and quality of life [25] [26] [27]. Patient and families are increasingly implicated in planning of care, and information about the possibility of conservative renal care by health care providers [28] [29]. It is likely that these factors will influence the uptake of conservative care over time.…”
Section: Countrymentioning
confidence: 99%